2019
DOI: 10.18070/erciyesiibd.569638
|View full text |Cite
|
Sign up to set email alerts
|

Türk ekonomisinde bütçe açığı ve enflasyon ilişkisinin sınır testi yaklaşımı ile eş-bütünleşme analizi

Abstract: In this study, the long-term relationship between budget deficits and inflation in the Turkish economy is analyzed by monthly data covering the period 2006:01-2018:10. Econometric methods used in the study; Expanded Dickey Fuller, Phillips-Perron an Ng-Perron unit root tests and a bonds testing approach. The main findings of the study; in the long term inflation between dolar exchange rate and M3 money supply statistically significant positive direction; a negative direction with the budget balance is to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In other words, increasing budget deficits increases the inflation rate. The inference in question, as obtained from various country examples by Narayan et al (2006), Devapriya and Ichihashi (2012), Isaq and Mohsin (2015), Nguyen (2015), and Arjomand et al (2016), has been reached through studies conducted within the scope of Turkiye by Metin (1995Metin ( , 1998, Akçay et al (1996), Günaydın (2004), Oktayer (2010), Bayrak and Kanca (2013), Bedir and Tural (2014), İpek and Akar (2016), Öruç (2016), Alper (2018), Maraş andDumrul (2019), andErdil Şahin (2019). Contrary to the aforementioned studies, no study has been found that concludes that increasing the budget deficit reduces the inflation rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, increasing budget deficits increases the inflation rate. The inference in question, as obtained from various country examples by Narayan et al (2006), Devapriya and Ichihashi (2012), Isaq and Mohsin (2015), Nguyen (2015), and Arjomand et al (2016), has been reached through studies conducted within the scope of Turkiye by Metin (1995Metin ( , 1998, Akçay et al (1996), Günaydın (2004), Oktayer (2010), Bayrak and Kanca (2013), Bedir and Tural (2014), İpek and Akar (2016), Öruç (2016), Alper (2018), Maraş andDumrul (2019), andErdil Şahin (2019). Contrary to the aforementioned studies, no study has been found that concludes that increasing the budget deficit reduces the inflation rate.…”
Section: Literature Reviewmentioning
confidence: 99%